Predictive ability of serum advanced glycation end products at 11 to 13 weeks of gestation for early-onset preeclampsiaAJOG Global Reports at a Glance - Minako Goto, MD; Sho-ichi Yamagishi, MD; Takanori Matsui, PhD; Keiko Koide, MD; Hiroko Takita, MD; Mayumi Tokunaka, MD; Akihiko Sekizawa, MD (Elsevier, 2022)
BACKGROUND: Placental hypoxia and resultant oxidative stress have been associated with the development of preeclampsia. Oxidative stress promotes the formation of advanced glycation end products. OBJECTIVE: This study aimed to assess whether serum levels of advanced glycation end products during the early stage of pregnancy are a predictive biomarker of early-onset and late-onset preeclampsia. STUDY DESIGN: This was a nested case-control study that included 6 women with early-onset preeclampsia, 21 women with late-onset preeclampsia, and 50 age- and body mass index-matched healthy female control subjects. All women enrolled in the study had a complete medical history, including mean arterial pressure and uterine artery pulsatility index measurements. Furthermore, the women underwent blood chemistry analysis, including circulating levels of advanced glycation end products, soluble fms-like tyrosine kinase-1, and placental growth factor. Clinical measurements and biochemistry were evaluated at 11 to 13 and 19 to 24 weeks of gestation. RESULTS: The median serum concentrations of advanced glycation end products at 11 to 13 weeks of gestation were significantly higher in patients with early-onset preeclampsia than in those with late-onset preeclampsia and control subjects (6.62 vs 4.10 vs 3.77; P<.05), but no significant difference was found in advanced glycation end products at 19 to 24 weeks of gestation among the 3 groups. The advanced glycation end product-to-placental growth factor ratio in the first trimester of pregnancy was significantly higher in patients with early-onset preeclampsia than in those with late-onset preeclampsia or control subjects (0.78 vs 0.10 vs 0.10; P<.05). The area under the receiver operating characteristic curve values for patients with early-onset preeclampsia were 0.782 (95% confidence interval, 0.522-0.922), 0.855 (95% confidence interval, 0.433-0.978), and 0.925 (95% confidence interval, 0.724-0.983) for the advanced glycation end product and placental growth factor levels and advanced glycation end product-to-placental growth factor ratios, respectively. This population achieved a 100% detection rate for predicting early-onset preeclampsia at a screen-positive rate of 10% by combining the advanced glycation end product-to-placental growth factor ratio and the mean arterial pressure. CONCLUSION: The study results suggested that an elevated advanced glycation end product-to-placental growth factor ratio and mean arterial pressure at 11 to 13 weeks of gestation could be a potential biomarker for predicting the future development of early-onset preeclampsia.